A PENGARUH FAKTOR USIA IBU TERHADAP PENGETAHUAN PEMBERIAN MAKANAN PENDAMPING ASI PADA BAYI USIA 6-12 - Ida Susila (Akademi Kebidanan Griya Husada Surabaya, 2018)
Introduction: Based on Household Health Survey (SKRT) states that under 6 months of age has been given complementary feeding of milk, so it can lead to various health problems in infants, such as diseases of the digestive system. the purpose of this study is to know the description of mother's knowledge about the provision of complementary feeding of milk in infants aged 6-12 months. Method: This research is descriptive research. The population in this study were mothers who had infants aged 6-12 months in RW 02 Village Sidokepung Buduran District Sidoarjo District. A total of 45 respondents. The sample size was 40 respondents. Data were collected using questionnaires. Sampling using probability sampling technique with simple random sampling technique, data analysis in the form of tables and cross tabulation. Result: The results showed that mothers aged > 35 years are well knowledgeable (16.7%). Discussion: After processed in percentage, it can be concluded that mother's knowledge about complementary feeding of baby at age 6-12 months is less. Suggestions for health workers to further improve counseling about the purpose of complementary feeding, and timing for complementary feeding, so that mothers understand the risks of complementary feeding when not on time. Keywords : Knowledge, age, Breastfeeding Companion